Biofilm Research in Bovine Mastitis - Pedersen, Regitze Renee; Krömker, Volker; Bjarnsholt, Thomas; Dahl-Pedersen, Kirstin; Buhl, Rikke; Jørgensen, Elin (Frontiers in Veterinary Science, 2021)
Bovine mastitis is one of the most important diseases in the dairy industry and has detrimental impact on the economy and welfare of the animals. Further, treatment failure results in increased antibiotic use in the dairy industry, as some of these mastitis cases for unknown reasons are not resolved despite standard antibiotic treatment. Chronic biofilm infections are notoriously known to be difficult to eradicate with antibiotics and biofilm formation could be a possible explanation for mastitis cases that are not resolved by standard treatment. This paper reviews the current literature on biofilm in bovine mastitis research to evaluate the status and methods used in the literature. Focus of the current research has been on isolates from milk samples and investigation of their biofilm forming properties in vitro. However, in vitro observations of biofilm formation are not easily comparable with the in vivo situation inside the udder. Only two papers investigate the location and distribution of bacterial biofilms inside udders of dairy cows with mastitis. Based on the current knowledge, the role of biofilm in bovine mastitis is still unclear and more in vivo investigations are needed to uncover the actual role of biofilm formation in the pathogenesis of bovine mastitis.